EMPTY BOX AS SYMBOLIC ACTION: YOUNG VOTERS’ REJECTION OF THE SOLE CANDIDATE IN GRESIK’S LOCAL - Erfina Dwi; Agus Machfud Fauzi; Rizky Trisna Putri (Universitas Negeri Semarang, 2025)
This study explores the symbolic meaning behind the choice of the